Return on Asset, Debt Equity Ratio, dan Dewan Pengawas terhadap Islamic Social Reporting pada Bank Syariah - Euis Nurawaliyah; Rina Destiana; Apri Dwi Astuti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Albeit the number of investigation of the syaria banking performance, its assessment viewed from the perspectives of return on asset, debt equity ration and supervising board share little evidence from the Indonesian corner. Thus, this paper aims to investigate the impact of return on asset, debt equaty ratio, and supervising board on the Islamic social reporting of syaria banking in Indonesia. Data were garnered from 9 syaria bank annual report in Indonesia published in 2015-2019. All data were officially released in gallery of Indonesian Stock Exchange. All data were statistically analyzed to reveal the impact of return on asset, debt equity ratio on Islamic social reporting. The findings show no impact of investigated variables on the performance of syaria bank Islamic social reporting.